Business Analytics and Data Science on Day 1 - Deza, Alfredo; Deza, Alfredo; Gift, Noah (Pragmatic AI Solutions, 2021)
Learn to get started on the right setup on your first day as a data scientist or business analytics professional. Topics include: * Business Analytics * Data Science * Google Colab * Jupyter * Github Actions and Github Codespaces * Continuous Integration and Delivery * EDA * GCP * AWS * Azure.